Sylvia Plath’s Poetry in Multiple Versions: A Case Study of UK School Anthologies - Julie Blake (Transatlantica)
The history of poetry anthologies created for use in compulsory nation-state education is largely untold. As material objects, school anthologies tend to be regarded as low status and ephemeral. Yet these objects have a lasting impact, as they facilitate encounters that are formative in shaping public understanding of poetry. This paper illustrates how two poems that are commonly featured in school poetry anthologies, Sylvia Plath’s “You’re” and “Morning Song,” encode a historical rationale for their material form in their bibliographic practices. It shows how “You’re” and “Morning Song” became “enregistered” (Agha 190) as acceptable tokens for the discussion of motherhood and domestic relationships by school-based adolescent readers with different social valuings of poetry and different levels of literacy. The case study of these two poems illuminates how poems in their multiple versions become established within a long-lasting and pervasive pedagogical canon of poetry. As such, the multiple pedagogical versions of poems have a value in constructing a complete story of the everyday “afterlife” of a poet’s work.